2020
DOI: 10.1128/mcb.00537-19
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP K Supports High-Amplitude D Site-Binding Protein mRNA (Dbp mRNA) Oscillation To Sustain Circadian Rhythms

Abstract: Circadian gene expression is defined by the gene-specific phase and amplitude of daily oscillations in mRNA and protein levels. D site-binding protein mRNA (Dbp mRNA) shows high-amplitude oscillation; however, the underlying mechanism remains elusive. Here, we demonstrate that heterogeneous nuclear ribonucleoprotein K (hnRNP K) is a key regulator that activates Dbp transcription via the poly(C) motif within its proximal promoter. Biochemical analyses identified hnRNP K as a specific protein that directly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Previously, we reported that the protein oscillation of hnRNP K drives Dbp and its downstream mRNA oscillation. 7 Furthermore, we demonstrated that RORγ and its downstream metabolic genes such as GluT2 and Elovl3 are also supported by hnRNP K. Taken together, we propose that hnRNP K is a key factor to elicit the transcriptional activation of Dbp and RORγ, which contribute to the maintenance of robust circadian rhythms. Interestingly, it was previously reported that hnRNP K functions as an mRNA stabilizer of Per3, which maintains its mRNA oscillation in a post-transcriptional way.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Previously, we reported that the protein oscillation of hnRNP K drives Dbp and its downstream mRNA oscillation. 7 Furthermore, we demonstrated that RORγ and its downstream metabolic genes such as GluT2 and Elovl3 are also supported by hnRNP K. Taken together, we propose that hnRNP K is a key factor to elicit the transcriptional activation of Dbp and RORγ, which contribute to the maintenance of robust circadian rhythms. Interestingly, it was previously reported that hnRNP K functions as an mRNA stabilizer of Per3, which maintains its mRNA oscillation in a post-transcriptional way.…”
Section: Discussionmentioning
confidence: 59%
“…Treatment with glycine (0.125 M) was performed for 10 minutes to stop the reaction of fixation following the treatment of 1% formaldehyde in NIH3T3 cells. Chromatin immunoprecipitation (ChIP) assays were performed as previously described 7,28 . Anti‐hnRNP K antibody (Abcam, ab70492) and anti‐RNAPII (Abcam, 8WG16) were added to the lysate to immunoprecipitate hnRNP K and RNAPII.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cerebellar cortex, Dbp is rhythmically expressed with an acrophase at the onset of the active period in rats fed ad libitum (Rath et al, 2012). Interestingly, Hnrnpk activates the transcription of Dbp and possibly of clock proteins (Kwon et al, 2020). Therefore, it is tempting to speculate that the elevated expression of given isoforms of Hnrnpk in the cerebellum of daytime food-restricted mice prior to meal time (i.e., spot 554) participates to some extent to feeding-induced shift of the cerebellar clockwork.…”
Section: Effects Of Feeding Conditions On Cerebellar Proteinsmentioning
confidence: 99%